Complexifying the Historiographical Perspective: Epistemic and Methodological tools for a History of Psy Knowledge - Benítez, Sebastián Matías; Molinari, Victoria; Nahmod, Maia; García, Luciano Nicolás; Briolotti, Ana; Ni, Mónica; Carreño, Sebastián; Macchioli, Florencia Adriana (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The aim of this article is to present and analyse a series of conceptual tools for a critical approach to the history of psychology, psychiatry and psychoanalysis. This article examines the growth of the field of the history of psi knowledge in the Ibero-American context, recovering the contributions of studies on the circulation of knowledge, the distinction between centres and peripheries and transnational perspectives. Considering the contribution of Critical Epistemology, it is important to establish the research problem by complexifying the instruments of analysis. A new field of research is presented, and a specific problem is outlined which allows us to account for the use of this conceptual and historiographical apparatus: R. Senet’s ideas about argentinian boys’ development and education at the beginning of the 20th century